Development of Independent Industrial IoT (IIoT) Device for Closed Building Application - Loo, Jun Xian; AZLINA BINTI BAHARI; AMIRUL SYAFIQ BIN SADUN (Progress in Engineering Application and Technology, 2025)
This thesis, titled "Development of Independent Industrial IoT (IIoT) Device for Closed Building Applications," explores the creation of a self-sustaining IoT device designed to monitor temperature and humidity in closed building environments. The primary goal is to develop an IoT device that operates independently of the building's Wi-Fi and power sources, ensuring uninterrupted data collection and transmission, particularly in environments with limited or unreliable local networks and power supplies.The device, constructed using an ESP32 microcontroller, a 3000mAh LiPo battery, an FS-MCore-F800 Series GSM module, and a DHT22 temperature and humidity sensor, leverages the GSM module to transmit data to the Node-Red platform and MySQL database. This eliminates the need for a local Wi-Fi network while enabling real-time monitoring. Testing demonstrated reliable, continuous sensing and transmission of temperature and humidity data, validating the device's effectiveness and consistent server communication.The successful implementation provides a proof of concept for autonomous sensors in industrial applications, particularly in scenarios requiring continuous monitoring without access to traditional power or network infrastructure. Insights gained from this research offer a foundation for advancing industrial IoT solutions.